2007
DOI: 10.1089/neu.2007.0306
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Reduces Contusion Volume after Controlled Cortical Impact Injury in Rats

Abstract: Recent data suggest that ubiquitin has anti-inflammatory properties and therapeutic potential after severe trauma and brain injuries. However, direct evidence for its neuroprotective effects has not yet been provided. We hypothesized that ubiquitin treatment is neuroprotective, and thus reduces brain edema formation and cortical contusion volume after closed traumatic brain injuries. To test this hypothesis, a focal cortical contusion was induced using a controlled cortical impact (CCI) model in Sprague-Dawley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
7
29
0
Order By: Relevance
“…It also prevented the increase in blood lactate levels that was detectable in animals after vehicle and AMD3100 administration, suggesting that CXCR4 activation with exogenous ubiquitin normalizes impaired tissue metabolism during the shock phase (66)(67)(68)(69). Thus, in combination with the therapeutically relevant effects of SDF-1α, SDF-1α-derived proteins and ubiquitin, which have been reported previously (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), the findings from the present study further point toward CXCR4 as a promising drug target for trauma patients. …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…It also prevented the increase in blood lactate levels that was detectable in animals after vehicle and AMD3100 administration, suggesting that CXCR4 activation with exogenous ubiquitin normalizes impaired tissue metabolism during the shock phase (66)(67)(68)(69). Thus, in combination with the therapeutically relevant effects of SDF-1α, SDF-1α-derived proteins and ubiquitin, which have been reported previously (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), the findings from the present study further point toward CXCR4 as a promising drug target for trauma patients. …”
Section: Resultssupporting
confidence: 83%
“…AMD3100 (generic name Plerixafor) was approved by the U.S. Food and Drug Administration to be used in combination with granulocytecolony stimulating factor to mobilize hematopoietic stem cells to the bloodstream in patients with non-Hodgkin lymphoma and multiple myeloma (36). On the basis of available data on the role of endogenous extracellular ubiquitin after trauma in patients (16,17), its inhibitory effects on leukocyte function upon pattern recognition receptor (PRR) activation (16,25,37) and the therapeutically relevant actions of CXCR4 agonists in various animal models (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), we hypothesized that blockade of ligand binding to CXCR4 will enhance proinflammatory responses of leukocytes and result in adverse effects when animals are subjected to severe trauma. Thus, we studied the pathophysiological response to trauma after blockade of CXCR4 with AMD3100 in a large animal model, which was designed to mimic the typical blunt polytrauma patient.…”
Section: Initial Assessment Of the Role Of CXC Chemokine Receptor 4 Amentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of the cognate ligand of CXCR4, stromal cell-derived factor-1␣ (SDF-1␣; chemokine (CXC motif) ligand 12) and of ubiquitin has been shown to result in anti-inflammatory and organ protective effects in various disease models (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Despite these similarities, we showed previously that ubiquitin, unlike SDF-1␣, does not reduce HIV-1 infectivity (23).…”
mentioning
confidence: 99%
“…This opinion seems not to be in line with data published by Sixt et al [12], indicating that: 'cell damage and haemolysis are the major sources of the increased extracellular ubiquitin concentrations measured under various pathological conditions' [66][67][68][69]. Conversely, Roth et al [64] concluded that because no significantly elevated proteasome concentrations after abdominal surgery and high levels of proteasome are found in patients suffering from trauma and sepsis, the cause of increased levels of 20S proteasome is immunological activity, rather than cellular damage.…”
Section: Discussionmentioning
confidence: 85%